Two-pronged strategy: Energizing bifunctional polyarylamine ketones in electrochromic supercapacitors - Wang, Qilin; Zheng, Zhibo; Shen, Huilin; Han, Yuntao; Chen, Zheng; Jiang, Zhenhua (Journal of alloys and compounds, 2025)
With the objective to actualize the lightweight and intelligent criteria in implementation and to extend the application range of high-performance polymers, a selection comprising polyarylamine ketone (PAAK) has been designed and synthesized as electrochromic materials. The remarkable photoelectric function of triphenylamine moieties and high-performance polymer characteristics were appropriately matched. And the synthesis method generalizability was confirmed through several attempts of side-chain substituent adjustment. The benefits of V2O5 nanowire ion storage layers in conjunction with the donor-acceptor (D-A) molecular engineering strategy deftly balanced electrochromic and energy storage features. Amongst them, devices employing PAAK-TPPA-OMe retained electrochromic performance subject to a 30,000-second switching. It was accessible to enhance the coloration efficiency to 331.19 cm2/C and reduce coloring time to 1.48 s after optimization. Likewise, PAAK-TPPA-OMe/V2O5 ECS yielded an area specific capacitance of 462.3 μF/cm2 and an energy density of 146.8 mWh/cm2 at a current density of 0.01 mA/cm2. It was convinced that such a conception could guide the intelligent integration of high-performance polymer functionalities. [Display omitted] •Series of intelligent materials derived from PAAKs have been designed and synthesized.•The system features a highly adjustable D-A structure.•The rational device structure enables color change and energy storage integration.•The coloring time for PAAK-TPPA-OMe/V2O5 ECS after optimization is merely 1.48 s.•The PAAK-TPPA-OMe/V2O5 ECS can operate continuously for more than 30,000 s.